LEVEL OF PATIENT SATISFACTION WITH THE QUALITY OF SERVICES AT LEPO-LEPO KENDARI PUSKESMAS DENTAL POLY DURING THE COVID-19 PANDEMIC - Nia Afdillah; Nuraisya Nuraisya; Widya Astuti (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Background: The quality of health services is a very important thing in the delivery of health services in order to show the degree of perfection of health services. Good service quality can lead to a sense of satisfaction for patients. Measuring the quality of service in a health facility can be done by assessing the level of patient satisfaction, where the patient is an object that directly enjoys the services provided. At the time when the COVID-19 pandemic caused disruption to public access to services, every health facility had to improve the quality of service to prevent transmission which could save the lives of patients and dentists. Purpose: This study aims to describe the level of patient satisfaction with the quality of service during a pandemic covid-19 at the dental polyclinic at the Lepo-Lepo Kendari Health Center. Research method: This type of research is descriptive in nature with a total sample of 50 people (total sample) who are visitors or patients at the dental polyclinic at the Lepo-Lepo Public Health Center. Results: the results of this study showed that 48% of patients were satisfied on the assurance dimension, 54% of patients were satisfied on the effectiveness dimension of health services, 56% of patients were satisfied on the dimensions of health services (responsiveness), 60% of patients were satisfied on the convenience dimension (physical appearance) and 58% of patients were satisfied on the human relations dimension (empathy). Conclusion: Overall from the five dimensions, the level of patient satisfaction with the quality of service at the dental polyclinic at the Lepo-Lepo Public Health Center is in the satisfied category.